Carbon Paper as a Promising Free Standing Anode for Sodium Ion Batteries. Issue 16 (21st December 2020) - Waseem, Sadiya; Nithya, C.; Maheshwari, Priyanka H.; Dhakate, S. R.
Abstract : Porous conducting carbon fiber composite papers have been developed by a two-step process. This involves fabrication of carbon fiber preform followed by composite formation. Different composite papers have been developed by varying the final heat treatment temperature of the composite, viz. 800 °C, 1100 °C, 1400 °C, 1800 °C and 2300 °C. The study gives an insight as to how the structure, porosity, morphology, electrical and mechanical properties of the carbon/carbon composites vary with temperature; and further the effect of these variations on the performance of the composites as anode material for Na-ion batteries. The sample heat-treated to 800 °C showed high reversible capacity of 278 mAh g −1 at a current density of 37 mA g −1 . Additionally, high columbic efficiency (>99%) and 72% retention of the initial capacity has been demonstrated for 1000 cycles. This exceptional performance is attributed to the small crystallite size, large d-spacing and disordered structure of the sample which favors the insertion/de-insertion of sodium ion into the composite anode. Hence, it seems as a promising anode material for sodium-ion batteries.